Molecular Characterisation of α- and β-Thalassaemia among Indigenous Senoi Orang Asli Communities in Peninsular Malaysia - Koh D.X.R.; Raja Sabudin R.Z.A.; Mohd Yusoff M.; Hussin N.H.; Ahmad R.; Othman A.; Ismail E. (Blackwell Publishing Ltd, 2024)
Indexed by Scopus/ERA